ANALISIS PELAKSANAAN MONITORING NASABAH PEMBIAYAAN BANK PEMBIAYAAN RAKYAT SYARIAH AMANAH UMMAH, KABUPATEN BOGOR, JAWA BARAT, PADA MASA PANDEMI COVID-19 - Rafiduddin; Trihantana, Rully; Kusumaningrum, Ria (SAHID BANKING JOURNAL, 2024)
Since the Covid-19 pandemic, the decline in business activities of BPRS Amanah Ummah customers has had an impact on the ability to pay installment obligations or the emergence of problematic financing. So that the financing monitoring process runs tighter than usual. The purpose of this study is to analyze and find out the course of financing monitoring activities at BPRS Amanah Ummah and how to resolve problematic financing. The research method used in this research is a qualitative method. Qualitative method is a research method that produces descriptive data in the form of written or spoken results from people or behavior that can see and pay attention to a research result. With this research it can be concluded that the financing monitoring function at the BPRS Amanah Ummah is running well. Because, even though we are in a pandemic, the NPF ratio is still within normal limits or 1% ≤, namely 3.74% in 2020 and 2.83% in 2021.